Polyethylene hollow fiber and preparation method thereof

By using carboxylated and esterified carbon nanotube reinforcer in polyethylene hollow fibers and performing triple-stage thermal stretching and aldehyde-based silica cross-linking treatment, the existing polyethylene hollow fibers are solved, and polyethylene hollow fibers with high strength, high toughness and good acid corrosion resistance are achieved.

CN119877133AInactive Publication Date: 2025-04-25SHANDONG MUDUN AVIATION TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411884439.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing polyethylene hollow fibers have low strength and elongation at break, and have poor corrosion resistance in acid liquid environments, which limits its application range.

Method used

Carbon nanotubes are used as fiber reinforcement agents to enhance the compatibility of carbon nanotubes with polyethylene by carboxylation and esterification treatment, and then primary hollow fibers are prepared and cross-linked by triple-stage thermal stretching and aldehyde-based silica to form a stable cross-linked network structure.

Benefits of technology

It significantly improves the tensile strength, tensile modulus and elongation of break of polyethylene hollow fibers, and maintains excellent acid corrosion resistance in an acid liquid environment, expanding its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a polyethylene hollow fiber and a preparation method thereof, and belongs to the field of polyethylene fibers. The preparation method comprises the following steps: preparing a fiber reinforcing agent, mixing materials, preparing primary hollow fibers and performing post-treatment. The post-treatment step comprises the following steps: putting the primary hollow fiber into an ethanol solution, uniformly stirring, raising the temperature to 57-63 DEG C, adding formylated silicon dioxide, raising the temperature to 82-87 DEG C, stirring and reacting for 1.8-2.2 hours, filtering, washing and drying after the reaction is finished, and performing three-stage thermal stretching to obtain the polyethylene hollow fiber; the polyethylene hollow fiber prepared by the method is high in strength, good in toughness and excellent in acid corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polyethylene fibers, and in particular relates to a polyethylene hollow fiber and a preparation method thereof. Background Art

[0002] Polyethylene fiber is a fiber material obtained by melt spinning of polyethylene. It has high strength, good insulation and excellent chemical resistance. It is suitable for making bristle, flat wire or split fiber, and is used to make ropes, filter cloth, packaging cloth, etc.; hollow fiber refers to a chemical fiber with a tubular cavity in the fiber axis, which can bring light elasticity, good moisture permeability and comfortable warmth retention to the fabric. It can be used for winter clothes, bedding and padding flakes, etc., and can also be assembled into microfiltration, ultrafiltration, dialysis, gas separation, reverse osmosis devices, etc.

[0003] Polyethylene hollow fiber is a fiber with a tubular cavity made of polyethylene. It has the advantages of light weight, elasticity and good air permeability. It has important applications in the field of separation membranes. It has good corrosion resistance and temperature performance and is widely used in medical, textile, clothing and wastewater treatment fields.

[0004] The prior art generally uses a melt stretching method to prepare polyethylene hollow fibers, specifically, polyethylene and additives and other ingredients are mixed evenly and then melt-extruded, and then extruded through a hollow spinneret, and then stretched and shaped to obtain a hollow fiber; For example, CN118007425A discloses a hydrophilic UHMWPE hollow fiber and its preparation method and application. The specific preparation method is to put a mixed raw material containing UHMWPE resin powder into a screw extruder for melt extrusion, use nitrogen as the cavity fluid and air as the cooling medium, and extrude the melt from the annular hollow spinneret hole through a metering pump to obtain UHMWPE primary fiber, and then after heat treatment and cold stretching, the fiber is immersed in a solution tank containing a photoinitiator and a hydrophilic monomer and then continues to be hot stretched under ultraviolet irradiation conditions. After the hot stretching is completed, it is heat-set to obtain UHMWPE hollow fiber; wherein the mixed raw material includes UHMWPE powder, a flow modifier, and auxiliary additives; the flow modifier includes one or more of low molecular weight polyethylene, linear low density polyethylene, high density polyethylene, and polypropylene; the auxiliary additive includes one or more of a reinforcing agent and an antioxidant; the reinforcing agent includes one or more of silicon dioxide, boron nitride, organic montmorillonite, titanium dioxide, graphene, and carbon nanotubes.

[0005] The hollow fiber prepared by this method has good hydrophilicity, but due to its hollow structure, its strength performance is reduced, which limits its scope of use.

[0006] CN1888153A discloses a method for preparing hollow high-strength high-modulus polyethylene fibers, specifically, polyethylene powder and mineral oil are mixed, an antioxidant is added, the temperature is raised to 105-130°C for swelling, and the temperature is then raised to 160-200°C to obtain a spinning solution, and the spinning solution is ejected through a slit using an inserted tube spinneret, and after ejection, the spinning solution is quenched in a cold water bath through an air layer to form a hollow gel fiber, and then ultrasonically extracted in dichloromethane, and dried and stretched to obtain a hollow polyethylene fiber; The hollow polyethylene fiber produced by this patent has a breaking strength of 32.6 cN / dtex, a modulus of 1250 cN / dtex, and an elongation at break of 2.8%. Its elongation at break is low and its acid corrosion resistance is poor. After being immersed in an acid environment, its strength loss is relatively large. Summary of the invention

[0007] In order to solve the technical problems existing in the prior art, the present invention provides a polyethylene hollow fiber and a preparation method thereof, which has high strength, high elongation at break and excellent acid corrosion resistance.

[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions: A method for preparing a polyethylene hollow fiber includes preparing a fiber reinforcing agent, mixing materials, preparing a primary hollow fiber, and post-processing steps, and the specific operations are as follows: 1. Preparation of fiber reinforcement (1) Carboxylation The carbon nanotubes are placed in a mixed acid solution for ultrasonic dispersion, the ultrasonic time is 33-37 minutes, the ultrasonic power is 122-128W, the ultrasonic frequency is 30-34kHz, after the ultrasonic dispersion is completed, the temperature is raised to 63-67°C at a rate of 1.8-2.2°C / min, the temperature is kept stirred for 5.8-6.2 hours, and the carbon nanotubes are obtained by filtering, washing and drying. The particle size of the carbon nanotubes is 210-230 nm; The mixed acid solution is a mixture of concentrated sulfuric acid and concentrated nitric acid, the volume ratio of the concentrated sulfuric acid to the concentrated nitric acid is 2.8-3.2:1, the mass concentration of the concentrated sulfuric acid is 83-87%, and the mass concentration of the concentrated nitric acid is 75-80%; The mass volume ratio of the carbon nanotubes and the mixed acid solution is 11.7-12.3 g: 225-235 mL; (2) Esterification The ethanol solution is introduced into the reaction container, and then the carboxylated carbon nanotubes are added and stirred evenly, and then the hydroxyethyl chitosan solution is added, and stirred at 414-426 rpm for 47-53 minutes. After the stirring is completed, sodium hypophosphite is added, and the temperature is increased to 132-140° C. for reaction. The reaction time is 42-48 minutes. After the reaction is completed, the reaction is filtered, washed, and dried to obtain esterified carbon nanotubes; The mass ratio of the ethanol solution, carboxylated carbon nanotubes, hydroxylated chitosan solution, and sodium hypophosphite is 490-510:10.0-10.5:20.2-20.8:1.4-1.6; The mass concentration of the ethanol solution is 48-52%; The hydroxyethyl chitosan solution is a mixture of hydroxyethyl chitosan and acetic acid solution. The mass concentration of the hydroxyethyl chitosan solution is 18.0-22.0%, and the mass concentration of the acetic acid solution is 7.8-8.2%.

[0009] 2. Mixing The polyethylene, esterified carbon nanotubes, antioxidant 1076, oleic acid amide and ethylene bisstearamide are mixed and then homogenized. The homogenization time is 3.5-4.5 minutes, the homogenization pressure is 3.3-3.6 MPa, the homogenization times are 2 times, and after the homogenization is completed, a mixture is obtained; The mass ratio of the polyethylene, esterified carbon nanotubes, antioxidant 1076, oleic acid amide and ethylene bisstearic acid amide is 92.6-93.5:3.5-4.0:1.2-1.4:0.8-1.2:0.7-1.3.

[0010] 3. Preparation of Primary Hollow Fibers The mixed material is placed in a twin-screw extruder for melt extrusion at an extrusion temperature of 226-230°C and a screw speed of 295-306rpm. After being metered by a metering pump, it is extruded from a hollow annular spinneret, and then heat-treated at 108-112°C for 2.4-2.6h. After cooling, it is stretched at room temperature until the elongation is 120-140%, thereby obtaining primary hollow fibers.

[0011] 4. Post-processing The primary hollow fiber is put into an ethanol solution, stirred evenly, and then the temperature is raised to 57-63°C, and formaldehyde-modified silica is added, and then the temperature is raised to 82-87°C, and the reaction is stirred for 1.8-2.2 hours. After the reaction is completed, it is filtered, washed, and dried, and then three-stage heat stretching is performed at 98-103°C, 115-120°C, and 123-127°C, with a total stretching ratio of 23-25 ​​times, and the relative humidity of the ambient air during stretching is controlled to be 60-64%, to obtain a polyethylene hollow fiber; The mass ratio of the primary hollow fiber, the ethanol solution, and the formaldehyded silica is 10.0-10.5:195-206:2.6-2.8; The mass concentration of the ethanol solution is 28-32%; The preparation method of the aldehyded silicon dioxide comprises the following steps: adding silicon dioxide to an ethanol solution, then adding glycerol and polyethylene glycol 600, stirring at 38-42° C. for 0.8-1.2 hours, filtering and washing after the stirring is completed, then putting into deionized water, adding sodium periodate for stirring, stirring evenly, reacting in the dark for 5.8-6.2 hours, adding ethylene glycol to terminate the reaction, filtering and drying, and obtaining the aldehyded silicon dioxide; The particle size of the silicon dioxide is 160-180 nm; The mass ratio of the ethanol solution, silicon dioxide, glycerol, polyethylene glycol 600, deionized water, sodium periodate and ethylene glycol is 146-155:10.0-10.6:1.4-1.7:1.5-1.8:990-1010:7.0-7.4:20-25; The mass concentration of the ethanol solution is 23-27%.

[0012] A polyethylene hollow fiber is prepared by the above preparation method.

[0013] Compared with the prior art, the present invention has achieved the following beneficial effects: 1. The present invention adopts a specific method to prepare a fiber reinforcing agent to enhance the strength performance of the fiber, wherein carbon nanotubes are used as a reinforcing matrix, the carbon nanotubes are subjected to a carboxylation treatment, and then an esterification reaction is carried out with the hydroxyl groups of hydroxyethyl chitosan, so that the surface of the carbon nanotubes contains more ester hydrophobic groups, thereby enhancing the compatibility with polyethylene and improving the uniform dispersion of the mixture, thereby improving the homogeneity of the primary hollow fiber during the melt extrusion process, thereby achieving the strength enhancement effect of the carbon nanotubes on the polyethylene fiber and improving the fiber toughness, and then the primary hollow fiber is post-treated, wherein the aldehyde group of the aldehyde-modified silica is used as a cross-linking agent to carry out a cross-linking reaction on the amino group and the hydroxyl group on the primary hollow fiber, so that the polyethylene hollow fiber forms a stable cross-linked network structure, further enhancing the strength performance and toughness of the polyethylene hollow fiber, and enhancing the stability performance while ensuring light weight; 2. The polyethylene hollow fiber prepared by the present invention has a tensile strength of 35.9-36.7 cN / dtex, a tensile modulus of 1262-1268 cN / dtex, and an elongation at break of 3.8-4.1%; 3. The polyethylene hollow fiber prepared by the present invention is immersed in a 23wt% hydrochloric acid solution of 5 times its mass for 15 days, and the tensile strength is 34.8-36.0 cN / dtex, the tensile modulus is 1206-1235 cN / dtex, and the elongation at break is 3.6-4.0%. DETAILED DESCRIPTION

[0014] In order to more clearly understand the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described.

[0015] Example 1 1. Preparation of fiber reinforcement (1) Carboxylation 12.0 g of carbon nanotubes were placed in 230 mL of mixed acid solution for ultrasonic dispersion, the ultrasonic time was 35 min, the ultrasonic power was 125 W, and the ultrasonic frequency was 32 kHz. After the ultrasonic dispersion was completed, the temperature was raised to 65 ° C at a rate of 2.0 ° C / min, and the temperature was kept stirred for 6.0 h, and the carboxyl carbon nanotubes were obtained by filtration, washing, and drying. The particle size of the carbon nanotubes is 220 nm; The mixed acid solution is a mixture of concentrated sulfuric acid and concentrated nitric acid, the volume ratio of the concentrated sulfuric acid to the concentrated nitric acid is 3:1, the mass concentration of the concentrated sulfuric acid is 85%, and the mass concentration of the concentrated nitric acid is 78%; (2) Esterification 500 g of 50 wt% ethanol solution was introduced into the reaction container, and then 10.2 g of carboxylated carbon nanotubes were added and stirred evenly, and then 20.5 g of 20.0 wt% hydroxyethyl chitosan solution was added, and stirred at 420 rpm for 50 min. After the stirring was completed, 1.5 g of sodium hypophosphite was added, and the temperature was raised to 136 ° C for reaction. The reaction time was 45 min. After the reaction was completed, it was filtered, washed and dried to obtain esterified carbon nanotubes; The hydroxyethyl chitosan solution is a mixture of hydroxyethyl chitosan and acetic acid solution, and the mass concentration of the acetic acid solution is 8.0%.

[0016] 2. Mixing 93.0 g of polyethylene, 3.7 g of esterified carbon nanotubes, 1.3 g of antioxidant 1076, 1.0 g of oleic acid amide, and 1.0 g of ethylene bisstearamide were mixed and then homogenized. The homogenization time was 4.0 min, the homogenization pressure was 3.5 MPa, and the homogenization times were 2 times. After the homogenization was completed, a mixture was obtained.

[0017] 3. Preparation of Primary Hollow Fibers The mixed material was placed in a twin-screw extruder for melt extrusion at an extrusion temperature of 228°C and a screw speed of 300 rpm. After being metered by a metering pump, it was extruded from a hollow annular spinneret and then heat treated at 110°C for 2.5 hours. After cooling, it was stretched at room temperature until the elongation was 130%, thereby obtaining primary hollow fibers.

[0018] 4. Post-processing 10.3 g of primary hollow fiber was put into 200 g of 30 wt% ethanol solution, stirred evenly, and then the temperature was raised to 60°C. 2.7 g of formaldehyded silica was added, and then the temperature was raised to 85°C. The mixture was stirred for reaction for 2.0 h. After the reaction was completed, the mixture was filtered, washed, and dried, and then three-stage heat stretching was performed at 100°C, 118°C, and 125°C. The total stretching ratio was 24 times. The relative humidity of the ambient air during stretching was controlled to be 62%, and polyethylene hollow fiber was obtained. The preparation method of the aldehyde-modified silica is as follows: add 10.3 g of silica to 150 g of a 25 wt% ethanol solution, then add 1.5 g of propylene glycol and 1.7 g of polyethylene glycol 600, stir at 40° C. for 1.0 h, filter and wash after the stirring, then put into 1000 g of deionized water, add 7.2 g of sodium periodate and stir, stir evenly and react in the dark for 6.0 h, add 23 g of ethylene glycol to terminate the reaction, filter and dry to obtain the aldehyde-modified silica; The particle size of the silicon dioxide is 170 nm.

[0019] Example 2 1. Preparation of fiber reinforcement (1) Carboxylation 11.7 g of carbon nanotubes were placed in 225 mL of mixed acid solution for ultrasonic dispersion, the ultrasonic time was 33 min, the ultrasonic power was 122 W, the ultrasonic frequency was 30 kHz, after the ultrasonic dispersion was completed, the temperature was raised to 63 ° C at a rate of 1.8 ° C / min, the temperature was kept stirred for 5.8 h, and the carboxyl carbon nanotubes were obtained by filtration, washing and drying; The particle size of the carbon nanotubes is 210 nm; The mixed acid solution is a mixture of concentrated sulfuric acid and concentrated nitric acid, the volume ratio of the concentrated sulfuric acid to the concentrated nitric acid is 2.8:1, the mass concentration of the concentrated sulfuric acid is 83%, and the mass concentration of the concentrated nitric acid is 75%; (2) Esterification 490 g of 48 wt% ethanol solution was introduced into the reaction container, and then 10.0 g of carboxylated carbon nanotubes were added and stirred evenly, and then 20.2 g of 18.0 wt% hydroxyethyl chitosan solution was added, and stirred at 414 rpm for 47 min. After the stirring was completed, 1.4 g of sodium hypophosphite was added, and the temperature was raised to 132 ° C for reaction. The reaction time was 42 min. After the reaction was completed, it was filtered, washed and dried to obtain esterified carbon nanotubes; The hydroxyethyl chitosan solution is a mixture of hydroxyethyl chitosan and acetic acid solution, and the mass concentration of the acetic acid solution is 7.8%.

[0020] 2. Mixing 92.6 g of polyethylene, 3.5 g of esterified carbon nanotubes, 1.2 g of antioxidant 1076, 0.8 g of oleic acid amide, and 0.7 g of ethylene bisstearamide were mixed and then homogenized. The homogenization time was 3.5 min, the homogenization pressure was 3.3 MPa, and the homogenization times were 2 times. After the homogenization was completed, a mixture was obtained.

[0021] 3. Preparation of Primary Hollow Fibers The mixed material was placed in a twin-screw extruder for melt extrusion at an extrusion temperature of 226°C and a screw speed of 295 rpm. After being metered by a metering pump, it was extruded from a hollow annular spinneret and then heat treated at 108°C for 2.6 hours. After cooling, it was stretched at room temperature until the elongation was 120%, thereby obtaining primary hollow fibers.

[0022] 4. Post-processing 10.0 g of primary hollow fiber was put into 195 g of 28 wt% ethanol solution, stirred evenly, and then the temperature was raised to 57° C., 2.6 g of formaldehyded silica was added, and the temperature was raised to 82° C., and the reaction was stirred for 2.2 h. After the reaction was completed, the solution was filtered, washed, and dried, and then three-stage heat stretching was performed at 98° C., 115° C., and 123° C. The total stretching ratio was 23 times, and the relative humidity of the ambient air during stretching was controlled to be 60%, to obtain polyethylene hollow fiber; The preparation method of the aldehyde-modified silica is as follows: add 10.0 g of silica to 146 g of 23 wt% ethanol solution, then add 1.4 g of propylene glycol and 1.5 g of polyethylene glycol 600, stir at 38° C. for 0.8 h, filter and wash after the stirring, then put into 990 g of deionized water, add 7.0 g of sodium periodate and stir, stir evenly and react in the dark for 5.8 h, add 20 g of ethylene glycol to terminate the reaction, filter and dry to obtain the aldehyde-modified silica; The particle size of the silicon dioxide is 160 nm.

[0023] Example 3 1. Preparation of fiber reinforcement (1) Carboxylation 12.3 g of carbon nanotubes were placed in 235 mL of mixed acid solution for ultrasonic dispersion, the ultrasonic time was 37 min, the ultrasonic power was 128 W, the ultrasonic frequency was 34 kHz, after the ultrasonic dispersion was completed, the temperature was raised to 67 ° C at a rate of 2.2 ° C / min, the temperature was kept stirred for 6.2 h, and the carboxyl carbon nanotubes were obtained by filtration, washing and drying; The particle size of the carbon nanotubes is 230 nm; The mixed acid solution is a mixture of concentrated sulfuric acid and concentrated nitric acid, the volume ratio of the concentrated sulfuric acid to the concentrated nitric acid is 3.2:1, the mass concentration of the concentrated sulfuric acid is 87%, and the mass concentration of the concentrated nitric acid is 80%; (2) Esterification 510 g of 52 wt% ethanol solution was introduced into the reaction container, and then 10.5 g of carboxylated carbon nanotubes were added and stirred evenly, and then 20.8 g of 22.0 wt% hydroxyethyl chitosan solution was added, and stirred at 426 rpm for 53 min. After the stirring was completed, 1.6 g of sodium hypophosphite was added, and the temperature was raised to 140 ° C for reaction. The reaction time was 48 min. After the reaction was completed, it was filtered, washed and dried to obtain esterified carbon nanotubes; The hydroxyethyl chitosan solution is a mixture of hydroxyethyl chitosan and acetic acid solution, and the mass concentration of the acetic acid solution is 8.2%.

[0024] 2. Mixing 93.5 g of polyethylene, 4.0 g of esterified carbon nanotubes, 1.4 g of antioxidant 1076, 1.2 g of oleic acid amide, and 1.3 g of ethylene bisstearamide were mixed and then homogenized. The homogenization time was 4.5 min, the homogenization pressure was 3.6 MPa, and the homogenization times were 2 times. After the homogenization was completed, a mixture was obtained.

[0025] 3. Preparation of Primary Hollow Fibers The mixed material was placed in a twin-screw extruder for melt extrusion at a temperature of 230°C and a screw speed of 306 rpm. After being metered by a metering pump, it was extruded from a hollow annular spinneret and then heat treated at 112°C for 2.4 h. After cooling, it was stretched at room temperature until the elongation was 140%, thereby obtaining primary hollow fibers.

[0026] 4. Post-processing 10.5 g of primary hollow fiber was added to 206 g of 32 wt% ethanol solution, and the temperature was raised to 63°C after stirring evenly. 2.8 g of formaldehyded silica was added, and the temperature was raised to 87°C. The mixture was stirred for reaction for 1.8 h. After the reaction was completed, the mixture was filtered, washed, and dried, and then subjected to three-stage heat stretching at 103°C, 120°C, and 127°C. The total stretching ratio was 25 times, and the relative humidity of the ambient air during stretching was controlled to be 64%, to obtain polyethylene hollow fiber. The preparation method of the aldehyde-modified silica is as follows: add 10.6 g of silica to 155 g of 27 wt % ethanol solution, then add 1.7 g of glycerol and 1.8 g of polyethylene glycol 600, stir at 42° C. for 1.2 h, filter and wash after the stirring, then put into 1010 g of deionized water, add 7.4 g of sodium periodate and stir, stir evenly and react in the dark for 6.2 h, add 25 g of ethylene glycol to terminate the reaction, filter and dry to obtain the aldehyde-modified silica; The particle size of the silicon dioxide is 180 nm.

[0027] Comparative Example 1 Based on Example 1, the changes are as follows: The preparation step of the fiber reinforcement is omitted, and in the mixing step, the fiber reinforcement is replaced by an equal amount of carbon nanotubes without any treatment, and the particle size of the carbon nanotubes is 220 nm; The rest of the operations are the same.

[0028] Comparative Example 2 Based on Example 1, the changes are as follows: In the post-treatment step, the aldehyde-modified silica is replaced by an equal amount of untreated silica, wherein the particle size of the silica is 170 nm; The rest of the operations are the same.

[0029] Performance Testing The performance tests of the polyethylene hollow fibers obtained in Examples 1-3 and Comparative Examples 1-2 were performed as follows:

[0030] The present invention adopts a specific method to prepare a fiber reinforcing agent to enhance the strength performance of the fiber. The method uses carbon nanotubes as a reinforcing matrix, performs a carboxylation treatment on the carbon nanotubes, and then performs an esterification reaction with the hydroxyl groups of hydroxyethyl chitosan, so that the surface of the carbon nanotubes contains more ester hydrophobic groups, enhances the compatibility with polyethylene, improves the uniform dispersion of the mixture, thereby improving the homogeneity of the primary hollow fiber during the melt extrusion process, and further realizes the strength enhancement effect of the carbon nanotubes on the polyethylene fiber, and improves the fiber toughness. Then, the primary hollow fiber is post-treated, and the aldehyde group of aldehyde-modified silica is used as a cross-linking agent to perform a cross-linking reaction on the amino group and the hydroxyl group on the primary hollow fiber, so that the polyethylene hollow fiber forms a stable cross-linked network structure, further enhancing the strength performance and toughness of the polyethylene hollow fiber, while ensuring light weight and enhancing stability.

[0031] In Comparative Example 1, in the mixing step, carbon nanotubes are directly mixed with polyethylene, the carbon nanotubes have strong agglomeration and poor dispersibility in the polyethylene matrix, the homogeneity of the obtained mixture is poor, and the primary hollow fiber obtained by melt extrusion has low strength and poor toughness, and its strength is uneven and the stability is poor. In Comparative Example 2, in the post-treatment step, untreated silica is used for post-treatment, which cannot adhere well to the surface of the primary hollow fiber, and the silica cannot be cross-linked with the hydroxyl and amino groups of the primary hollow fiber, so that the obtained polyethylene hollow fiber has poor stability, strength and toughness.

[0032] Unless otherwise specified, all ratios and percentages described in the present invention are by mass ratios and percentages are by mass percentages.

[0033] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a polyethylene hollow fiber, characterized in that: It includes steps of preparing fiber reinforcement, mixing materials, preparing primary hollow fibers, and post-processing; The preparation of the fiber reinforcing agent comprises carboxylation and esterification steps; The esterification step comprises: introducing an ethanol solution into a reaction container, then adding carboxylated carbon nanotubes and stirring evenly, then adding a hydroxyethyl chitosan solution, stirring at 414-426 rpm for 47-53 minutes, adding sodium hypophosphite after the stirring is completed, raising the temperature to 132-140° C. for reaction, and the reaction time is 42-48 minutes. After the reaction is completed, filtering, washing, and drying are performed to obtain esterified carbon nanotubes; The post-treatment step is to put the primary hollow fiber into an ethanol solution, stir it evenly, then raise the temperature to 57-63°C, add formaldehyded silica, and then raise the temperature to 82-87°C, stir and react for 1.8-2.2 hours, and after the reaction is completed, filter, wash and dry it, and then perform three-stage heat stretching to obtain polyethylene hollow fibers; The preparation method of the aldehyded silicon dioxide comprises the following steps: adding silicon dioxide to an ethanol solution, then adding glycerol and polyethylene glycol 600, stirring at 38-42° C. for 0.8-1.2 hours, filtering and washing after the stirring is completed, then putting into deionized water, adding sodium periodate for stirring, stirring evenly, reacting in the dark for 5.8-6.2 hours, adding ethylene glycol to terminate the reaction, filtering and drying, and obtaining the aldehyded silicon dioxide.

2. The method for preparing a polyethylene hollow fiber according to claim 1, characterized in that: The carboxylation step comprises placing the carbon nanotubes in a mixed acid solution for ultrasonic dispersion, wherein the ultrasonic time is 33-37 minutes, the ultrasonic power is 122-128W, and the ultrasonic frequency is 30-34kHz. After the ultrasonic dispersion is completed, the temperature is raised to 63-67°C at a rate of 1.8-2.2°C / min, and the temperature is kept stirred for 5.8-6.2 hours, and the carbon nanotubes are filtered, washed, and dried to obtain carboxyl carbon nanotubes. The particle size of the carbon nanotubes is 210-230 nm; The mixed acid solution is a mixture of concentrated sulfuric acid and concentrated nitric acid, the volume ratio of the concentrated sulfuric acid to the concentrated nitric acid is 2.8-3.2:1, the mass concentration of the concentrated sulfuric acid is 83-87%, and the mass concentration of the concentrated nitric acid is 75-80%; The mass volume ratio of the carbon nanotubes and the mixed acid solution is 11.7-12.3 g:225-235 mL.

3. The method for preparing a polyethylene hollow fiber according to claim 1, characterized in that: In the esterification step, the mass ratio of the ethanol solution, carboxylated carbon nanotubes, hydroxylated chitosan solution, and sodium hypophosphite is 490-510:10.0-10.5:20.2-20.8:1.4-1.6; The mass concentration of the ethanol solution is 48-52%; The hydroxyethyl chitosan solution is a mixture of hydroxyethyl chitosan and acetic acid solution, the mass concentration of the hydroxyethyl chitosan solution is 18.0-22.0%, and the mass concentration of the acetic acid solution is 7.8-8.2%.

4. The method for preparing a polyethylene hollow fiber according to claim 1, characterized in that: The mixing step comprises mixing polyethylene, esterified carbon nanotubes, antioxidant 1076, oleic acid amide, and ethylene bisstearamide, and then homogenizing the mixture. The homogenization time is 3.5-4.5 minutes, the homogenization pressure is 3.3-3.6 MPa, the homogenization times are 2 times, and after the homogenization is completed, a mixture is obtained. The mass ratio of the polyethylene, esterified carbon nanotubes, antioxidant 1076, oleic acid amide and ethylene bisstearic acid amide is 92.6-93.5:3.5-4.0:1.2-1.4:0.8-1.2:0.7-1.

3.

5. The method for preparing a polyethylene hollow fiber according to claim 1, characterized in that: The step of preparing the primary hollow fiber is to place the mixed material in a twin-screw extruder for melt extrusion, the extrusion temperature is 226-230° C., the screw speed is 295-306 rpm, and the mixed material is extruded from a hollow annular spinneret after being metered by a metering pump, and then heat-treated at 108-112° C. for 2.4-2.6 hours, and stretched at room temperature after cooling until the elongation is 120-140%, so as to obtain the primary hollow fiber.

6. The method for preparing a polyethylene hollow fiber according to claim 1, characterized in that: In the post-treatment step, the three-stage heat stretching is performed at 98-103° C., 115-120° C., and 123-127° C., with a total stretching ratio of 23-25 ​​times, and the relative humidity of the ambient air during stretching is controlled to be 60-64%.

7. The method for preparing a polyethylene hollow fiber according to claim 1, characterized in that: In the post-treatment step, the mass ratio of the primary hollow fiber, the ethanol solution, and the formaldehyde-modified silica is 10.0-10.5:195-206:2.6-2.8; The mass concentration of the ethanol solution is 28-32%.

8. The method for preparing a polyethylene hollow fiber according to claim 1, characterized in that: The preparation method of the aldehyde-modified silica is as follows: the particle size of the silica is 160-180 nm; The mass ratio of the ethanol solution, silicon dioxide, glycerol, polyethylene glycol 600, deionized water, sodium periodate and ethylene glycol is 146-155:10.0-10.6:1.4-1.7:1.5-1.8:990-1010:7.0-7.4:20-25; The mass concentration of the ethanol solution is 23-27%.

9. The polyethylene hollow fiber obtained according to the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Hydrophilic UHMWPE hollow fiber as well as preparation method and application thereof

    CN118007425A